Implementation of Medical Record Security and Confidentiality Aspects Based on Accreditation Standards at Imelda Pekerja Indonesia General Hospital, Medan - Abdul Malik Ritonga; Zulham Andi Ritonga; Geovani Arta sihite; Mei Sryendang Sitorus; Rasnita Suryanti Laia (Cattleya Darmaya Fortuna, 2026)
The security and confidentiality of medical records are essential aspects of protecting patients’ health information. This study aimed to describe the implementation of medical record security and confidentiality aspects based on accreditation standards at Imelda Pekerja Indonesia General Hospital, Medan. This study employed a qualitative research method. The informants consisted of four individuals: one head of the medical records unit, one medical records officer, and two information technology (IT) officers. Data were collected using an interview guide to obtain relevant information from the informants. The results showed that the implementation of medical record security and confidentiality at Imelda Pekerja Indonesia General Hospital, Medan, was generally well implemented, supported by established procedures related to data security and confidentiality, including Standard Operating Procedures (SOPs) for data backup, Hospital Information Management System (SIMRS) data protection, user account management, and access rights to medical records. It is expected that all personnel directly involved in maintaining the security and confidentiality of medical records will consistently safeguard such records to ensure that patients’ data are protected from unauthorized third parties.